Publications by Scandinavian university Departments of Anaesthesiology from 2001 to 2015. Issue 9 (29th May 2018) - Miller, C.; Prenn, R.; Ausserer, J.; Hamm, P.; Neururer, S.; Paal, P.
Abstract : Background: This study assessed the contribution made to research by Scandinavian university Departments of Anaesthesiology and their distribution among those departments. Methods: We committed a PubMed search for all publications originating from Scandinavian university Departments of Anaesthesiology between 2001 and 2015. Articles were assigned to their author's affiliated university department and to 3 time periods 2001‐2005, 2006‐2010 and 2011‐2015. The number of publications, original articles and citations were analysed. Results: The 23 Scandinavian university Departments of Anaesthesiology published 5190 articles between 2001 and 2015, which make up 91.5% from all anaesthesiology research originating from Scandinavia. Of these 1760 (33.9%) were classified as original articles. The number of publications increased in the observed periods (from 1305 in 2001‐2005 to 2452 in 2010‐2015), but the share of original articles decreased (from 40% to 31%). Finnish university Departments of Anaesthesiology had the largest share of original articles. The university department of Copenhagen was the most productive Department of Anaesthesiology in terms of number of publications (n = 1187) and citation rate of original articles (median 24 citations per original article). Publications from Bergen scored the highest impact (median 19 citations per publication). Conclusions: The number of publications from Scandinavian university Departments of Anaesthesiology increased between 2001 and 2015, but the share of original articles decreased. Copenhagen was the most productive university Department of Anaesthesiology based on the number of publications and citations of original articles. Finnish university Departments of Anaesthesiology led in the share of original articles out of all publications.